Resin composition

KR103012629B1Active Publication Date: 2026-09-01LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
KR1020200127536
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-29
Publication Date
2026-09-01
Estimated Expiration
2040-09-29

Smart Images

  • Figure 112020104298099-PAT00001
    Figure 112020104298099-PAT00001
  • Figure 112020104298099-PAT00002
    Figure 112020104298099-PAT00002
  • Figure 112020104298099-PAT00003
    Figure 112020104298099-PAT00003
Patent Text Reader

Abstract

The present application provides a resin composition that exhibits appropriate viscosity, thixotropy, and / or thermal conductivity before and after curing, appropriate adhesion capable of effectively holding multiple battery modules before and after curing, and reworkability capable of enabling the separation and reattachment of modules during the assembly process of a battery pack.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] This application relates to a resin composition. Background Technology

[0003] A thermal interface material (TIM) refers to any material inserted between two components to improve thermal bonding between them. Generally, thermal interface materials are used as heat dissipation materials. Among these heat dissipation materials, a resin composition in which a thermally conductive filler is blended into a resin is known, and Patent Document 1 describes a battery module to which the resin composition is applied.

[0004] Thermal interface materials may require low adhesion and room-temperature curability depending on the situation.

[0005] An example of a resin possessing these properties is silicone resin. Silicone resin is primarily used as a heat dissipation material due to its low adhesion, room-temperature curing properties, and excellent heat resistance; however, when low-molecular-weight siloxanes are used, there was a problem where VOCs (volatile organic compounds) adhered to the electrodes, causing contact failures.

[0006] Urethane resin or epoxy resin can be considered as an alternative to the contact failure problem. However, while both urethane and epoxy resins possess high adhesive strength, epoxy resin had the issue of requiring a long time for curing at room temperature. Prior art literature

[0008] Republic of Korea Published Patent Application No. 10-2016-0105354 The problem to be solved

[0009] The present application provides a resin composition as a thermal interface material that requires room temperature curing and has low adhesion (particularly to metals such as aluminum).

[0010] The present application aims to provide a resin composition that exhibits appropriate viscosity, thixotropy, and / or thermal conductivity before and after curing.

[0011] The present application aims to provide a resin composition that exhibits appropriate adhesion to effectively maintain multiple battery modules before and after curing, and at the same time, reworkability to enable the separation and reattachment of modules during the assembly process of a battery pack.

[0012] The present application also aims to provide a resin composition that exhibits room temperature curing and rapid curing properties even while containing an excess amount of filler. means of solving the problem

[0014] The present application relates to a resin composition that is a thermal interface material requiring room temperature curing and having low adhesion (particularly, low adhesion to metals such as aluminum).

[0015] In the present application, a urethane reaction may be used as the resin composition. In this case, a main component part including a polyol, etc., and a curing agent part including an isocyanate compound, etc., may react and cure at room temperature. That is, the composition of the present application may be a curable composition that is room temperature curable.

[0016] The term "room temperature" as used in this application may mean a temperature within the range of about 10°C to 30°C that is not specifically heated or cooled, for example, about 15°C or higher, about 18°C ​​or higher, about 20°C or higher, or about 23°C or higher and about 27°C or lower.

[0017] In one example of the present application, the resin composition may be a one-component composition in which a curing reaction occurs when specific conditions (e.g., temperature and UV irradiation, etc.) are satisfied while the main component part, the curing agent part, and a compound that inhibits their curing are mixed.

[0018] In one example of the present application, the resin composition may be a two-component composition in which the main component part and the curing agent part are mixed without mixing, and a curing reaction is carried out with the help of a catalyst or the like.

[0019] In one example of the present application, the resin composition may include a filler. For example, to ensure thixotropy as required for the process, and / or to ensure heat dissipation (thermal conductivity) within a battery module or battery pack, the composition of the present application may include an excess amount of filler as described below. Specific details are described in detail in the following related description.

[0020] Unless otherwise specified, the term alkyl group or alkylene group used in this application may be a straight-chain or branched-chain acyclic alkyl group or alkylene group having 1 to 20 carbon atoms, or 1 to 16 carbon atoms, or 1 to 12 carbon atoms, or 1 to 8 carbon atoms, or 1 to 6 carbon atoms; a cyclic alkyl group or alkylene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms; or a saturated hydrocarbon group to which these are combined.

[0021] Unless otherwise specified, the alkenyl group or alkenylene group used in this application may be a straight-chain or branched-chain acyclic alkenyl group or alkenylene group having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms; a cyclic alkenyl group or alkenylene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms, or an unsaturated hydrocarbon group to which these are combined.

[0022] Unless otherwise specified, the alkynyl group or alkynylene group used in this application may be a straight-chain or branched acyclic alkynyl group or alkynylene group having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms; a cyclic alkynyl group or alkynylene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms; or an unsaturated hydrocarbon group to which these are combined.

[0023] As used in this application, the term "aryl group" may refer to an aromatic ring from which one hydrogen has been removed from an aromatic hydrocarbon ring, unless otherwise specified. The aryl group may be monocyclic or polycyclic.

[0024] The term heteroaryl group as used in this application may refer to a substituent comprising an aromatic ring containing one or more heteroatoms (e.g., N, O, S, etc.) as ring-forming atoms, unless otherwise specified. The heteroaryl group may be monocyclic or polycyclic.

[0025] The above alkyl group, alkylene group, alkenyl group, alkenylene group, alkynyl group, alkynylene group, aryl group, or heteroaryl group may optionally be substituted by one or more substituents. In this case, the substituents may be one or more selected from the group consisting of halogen (chloro(Cl), iodine(I), bromo(Br), fluorine(F)), alkyl group, alkenyl group, alkynyl group, aryl group, heteroaryl group, ether group, and hydroxyl group, but are not limited thereto.

[0026] The term "thermal conductivity" as used in this application may mean a case where the resin composition exhibits a thermal conductivity of about 1.2 W / m·K or more when measured according to ASTM D5470 or ISO 22007-2 standards along the thickness direction of the sample, while in a state where the resin composition is made into a sample (cured product) with a diameter of 2 cm or more and a thickness of 500 μm.

[0027] The above thermal conductivity may be 1.3 W / m·K or higher, 1.4 W / m·K or higher, 1.5 W / m·K or higher, 1.6 W / m·K or higher, 1.7 W / m·K or higher, 1.8 W / m·K or higher, 1.9 W / m·K or higher, 2.0 W / m·K or higher, 2.1 W / m·K or higher, 2.2 W / m·K or higher, 2.3 W / m·K or higher, 2.4 W / m·K or higher, or 2.5 W / m·K or higher. Since a higher value indicates higher thermal conductivity, the upper limit is not specifically restricted. For example, the thermal conductivity may be 20 W / m·K or less, 18 W / m·K or less, 16 W / m·K or less, 14 W / m·K or less, 12 W / m·K or less, 10 W / m·K or less, 8 W / m·K or less, 6 W / m·K or less, or 5 W / m·K or less.

[0029] The resin composition according to the present application may comprise a main part having a polyol component; and a curing agent part having an isocyanate component.

[0030] 1. Topic Part

[0031] The resin composition according to the present application comprises a main part having a polyol component. The polyol component of the main part may be a polyester polyol, and using such a polyol is advantageous for ensuring appropriate adhesion and adhesion reliability after the resin composition is cured.

[0032] The polyol component of the subject part according to the present application may include a polymeric diol compound and a polymeric multiol compound. In this case, the diol compound refers to a compound containing two hydroxyl groups, and the multiol compound refers to a compound containing three or more hydroxyl groups. Furthermore, the term polymer refers to a number average molecular weight (M n It refers to a compound having a molecular weight of 200 g / mol or more. Here, the multiol compound is suitable as a triol compound containing three hydroxyl groups. Unless specifically otherwise specified, the number average molecular weight (M) in this application n ) can be measured using GPC (Gel Permeation Chromatography).

[0033] Polymeric diol compounds can be exemplified by polyethylene glycol and polypropylene glycol, but are not particularly limited as long as they contain two hydroxyl groups and have a number average molecular weight of 200 g / mol or more. In addition, even if the same type of polymeric diol compound is used, a mixture of compounds with different average molecular weights may be used.

[0034] Polymer triol compounds may be exemplified by polyethylenetriol and polypropylenetriol, but are not specifically limited as long as they contain three hydroxyl groups and have a number average molecular weight of 200 g / mol or more. In addition, even if the same type of polymer triol compound is used, a mixture of compounds with different average molecular weights may be used.

[0035] Likewise, polymeric multiol compounds other than polymeric triol compounds are not particularly limited in type as long as they contain four or more hydroxyl groups and have a number average molecular weight of 200 g / mol or more.

[0036] Polymeric diol compounds have a number average molecular weight (M n) may be approximately 300 g / mol or more, 400 g / mol or more, 500 g / mol or more, 600 g / mol or more, 700 g / mol or more, 800 g / mol or more, 900 g / mol or more, 1,000 g / mol or more, 1,500 g / mol or more, 2,000 g / mol or more, 2,500 g / mol or more, 3,000 g / mol or more, 3,500 g / mol or more, 4,000 g / mol or more, 4,500 g / mol or more, 5,000 g / mol or more, 5,500 g / mol or more, or 5,750 g / mol or more. Additionally, in another example, the polymeric diol compound has a number average molecular weight (M n ) may be approximately 6,000 g / mol or less, 5,500 g / mol or less, 5,000 g / mol or less, 4,500 g / mol or less, 4,000 g / mol or less, 3,500 g / mol or less, 3,000 g / mol or less, 2,500 g / mol or less, 2,000 g / mol or less, 1,500 g / mol or less, 1,000 g / mol or less, 900 g / mol or less, 800 g / mol or less, 700 g / mol or less, 600 g / mol or less, 500 g / mol or less, 400 g / mol or less, or 350 g / mol or less.

[0037] Polymeric multiol compounds have a number average molecular weight (M n) may be approximately 300 g / mol or more, 400 g / mol or more, 500 g / mol or more, 600 g / mol or more, 700 g / mol or more, 800 g / mol or more, 900 g / mol or more, 1,000 g / mol or more, 1,500 g / mol or more, 2,000 g / mol or more, 2,500 g / mol or more, 3,000 g / mol or more, 3,500 g / mol or more, 4,000 g / mol or more, 4,500 g / mol or more, 5,000 g / mol or more, 5,500 g / mol or more, or 5,750 g / mol or more. Additionally, in another example, the polymeric multiol compound has a number average molecular weight (M n ) may be approximately 6,000 g / mol or less, 5,500 g / mol or less, 5,000 g / mol or less, 4,500 g / mol or less, 4,000 g / mol or less, 3,500 g / mol or less, 3,000 g / mol or less, 2,500 g / mol or less, 2,000 g / mol or less, 1,500 g / mol or less, 1,000 g / mol or less, 900 g / mol or less, 800 g / mol or less, 700 g / mol or less, 600 g / mol or less, 500 g / mol or less, 400 g / mol or less, or 350 g / mol or less.

[0038] The content of the polymer multiol compound may be 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, or 50 wt% or more relative to the total weight of the polyol component, and in another example, the content of the polymer multiol compound may be 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, or 55 wt% or less relative to the total weight of the polyol component.

[0039] Additionally, the content of the polymeric diol compound may be 40 parts by weight or more, 45 parts by weight or more, 50 parts by weight or more, 55 parts by weight or more, 60 parts by weight or more, 65 parts by weight or more, 70 parts by weight or more, 75 parts by weight or more, or 80 parts by weight or more, relative to 100 parts by weight of the polymeric multiol compound, and in another example, the content of the polymeric diol compound may be 200 parts by weight or less, 150 parts by weight or less, 140 parts by weight or less, 130 parts by weight or less, 120 parts by weight or less, 110 parts by weight or less, 100 parts by weight or less, or 90 parts by weight or less, relative to 100 parts by weight of the polymeric multiol compound.

[0040] The range of content of the polymeric diol compound and the polymeric multiol compound is determined by considering the mixing with one or more compounds selected from the group consisting of alcohol compounds and thiol compounds described below. When the content of the polymeric diol compound and the polymeric multiol compound satisfies the above range, a resin composition having reworkability can be secured by achieving low adhesion, particularly to metals such as aluminum.

[0042] Either one of the polymeric diol compound and polymeric multiol compound of the polyol component may be a polyester polyol.

[0043] Number average molecular weight (M of polyester polyol) n ) can be adjusted considering appropriate viscosity, adhesion, and reworkability. For example, the number average molecular weight (M) of the polyester polyol n) may be approximately 300 g / mol or more, 400 g / mol or more, 500 g / mol or more, 600 g / mol or more, 700 g / mol or more, 800 g / mol or more, 900 g / mol or more, 1,000 g / mol or more, 1,500 g / mol or more, 2,000 g / mol or more, 2,500 g / mol or more, 3,000 g / mol or more, 3,500 g / mol or more, 4,000 g / mol or more, 4,500 g / mol or more, 5,000 g / mol or more, 5,500 g / mol or more, or 5,750 g / mol or more. Additionally, in another example, the number average molecular weight (M of the polyester polyol) n ) may be approximately 6,000 g / mol or less, 5,500 g / mol or less, 5,000 g / mol or less, 4,500 g / mol or less, 4,000 g / mol or less, 3,500 g / mol or less, 3,000 g / mol or less, 2,500 g / mol or less, 2,000 g / mol or less, 1,500 g / mol or less, 1,000 g / mol or less, 900 g / mol or less, 800 g / mol or less, 700 g / mol or less, 600 g / mol or less, 500 g / mol or less, 400 g / mol or less, or 350 g / mol or less. The number average molecular weight (M) of the polyester polyol may be n If ) is within the above range, problems related to volatile components can be improved.

[0044] The polyester polyol according to the present application may be, for example, a carboxylic acid-based polyol. The carboxylic acid-based polyol may be formed by reacting a carboxylic acid with a component comprising a compound having a polyfunctional hydroxyl group. In this case, the carboxylic acid may be a dicarboxyl acid.

[0045] The polyester polyol according to the present application may, in other examples, comprise a compound represented by the following chemical formula 1.

[0046] [Chemical Formula 1]

[0047]

[0048] In the above chemical formula 1, R1 may be an alkyl group, an alkenyl group, or an alkynyl group substituted or unsubstituted with a hydroxyl group.

[0049] Additionally, L1 and L2 may each independently be a single bond, an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that L1 and L2 each independently be an alkyl group having 1 to 8 carbon atoms, and it is more preferable that each independently be an alkyl group having 1 to 4 carbon atoms.

[0050] Also, l and m can each independently be integers in the range of 0 to 10, and l+m is 1 or greater. That is, l and m cannot be 0 at the same time, and if l is 0, m must be 1 or greater, and if m is 0, l must be 1 or greater.

[0051] Additionally, X1 and X2 may each independently be an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that X1 and X2 each independently be an alkyl group having 1 to 12 carbon atoms, and more preferable that each independently be an alkyl group having 3 to 9 carbon atoms.

[0052] Additionally, Y1 and Y2 may each independently be an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that Y1 and Y2 each independently be an alkyl group having 1 to 12 carbon atoms, and it is more preferable that each independently be an alkyl group having 1 to 8 carbon atoms.

[0053] In addition, R2 may be hydrogen, an alkyl group, an alkenyl group, an alkynyl group, or a functional group represented by the following chemical formula 2.

[0054] [Chemical Formula 2]

[0055]

[0056] In the above chemical formula 2, L3 may be a single bond, an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that L3 be an alkyl group having 1 to 8 carbon atoms, and more preferable that it be an alkyl group having 1 to 4 carbon atoms.

[0057] In addition, X3 may be an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that X3 be an alkyl group having 1 to 12 carbon atoms, and more preferable that it be an alkyl group having 3 to 9 carbon atoms.

[0058] In addition, Y3 may be an alkyl group, an alkenyl group, or an alkynyl group. It is preferable that Y3 be an alkyl group having 1 to 12 carbon atoms, and more preferable that it be an alkyl group having 1 to 8 carbon atoms.

[0059] In addition, n can be an integer in the range of 0 to 10.

[0060] l and m of Formula 1 and n of Formula 2 above may be selected considering the desired physical properties of the resin composition or its cured product. When l and m of Formula 1 and n of Formula 2 are within the above ranges, the injection processability of the composition can be improved while suppressing the crystallinity of the polyol component.

[0061] In addition, the polyester polyol according to the present application comprises a compound represented by the above chemical formula 1, and may also include two or more compounds of different types that fall within the category of chemical formula 1.

[0062] The content of the polyester polyol is preferably within the range of 30 to 70 weight%, 35 to 65 weight%, or 40 to 60 weight% relative to the total weight of the polyol, and if the content of the polyester polyol does not satisfy the above range, it is impossible to formulate and thus cannot form a cured product.

[0064] Among the polymeric diol compound and polymeric multiol compound of the polyol component, one may be a polyester polyol and the other may be a polyether polyol. The details regarding the polyester polyol are the same as those described above.

[0065] Number average molecular weight (M of polyether polyol) n ) is the number average molecular weight (M) of the polyester polyol n It can be determined according to ). The number average molecular weight (M) of a polyester polyol n1 ) and the number average molecular weight (M) of the polyether polyol n2 The ratio of ) (M n1 / M n2 ) may be in the range of 0.5 to 2. In another example, the number average molecular weight (M) of the polyester polyol n1 ) and the number average molecular weight (M) of the polyether polyol n2 The ratio of ) (M n1 / M n2 ) may be within the range of 0.75 to 1.5 or within the range of 0.8 to 1.25. Number average molecular weight (M) of polyester polyol n1 ) and the number average molecular weight (M) of the polyether polyol n2 The ratio of ) (M n1 / M n2 If the above range is satisfied, the appropriate viscosity, adhesion, and reworkability of the resin composition can be secured.

[0066] Number average molecular weight (M of polyether polyol) n) may be about 300 g / mol or more, 400 g / mol or more, 500 g / mol or more, 600 g / mol or more, 700 g / mol or more, 800 g / mol or more, 900 g / mol or more, 1,000 g / mol or more, 1,500 g / mol or more, 2,000 g / mol or more, 2,500 g / mol or more, 3,000 g / mol or more, 3,500 g / mol or more, 4,000 g / mol or more, 4,500 g / mol or more, 5,000 g / mol or more, 5,500 g / mol or more, or 5,750 g / mol or more, while satisfying the ratio with the number average molecular weight of the polyester polyol. In addition, in another example, the number average molecular weight (M) of the polyether polyol n While satisfying the ratio with the number average molecular weight of the polyester polyol, ) may be about 6,000 g / mol or less, 5,500 g / mol or less, 5,000 g / mol or less, 4,500 g / mol or less, 4,000 g / mol or less, 3,500 g / mol or less, 3,000 g / mol or less, 2,500 g / mol or less, 2,000 g / mol or less, 1,500 g / mol or less, 1,000 g / mol or less, 900 g / mol or less, 800 g / mol or less, 700 g / mol or less, 600 g / mol or less, 500 g / mol or less, 400 g / mol or less, or 350 g / mol or less.

[0067] Polyether polyols may be polyalkylene glycols. Examples include, but are not limited to, polyethylene glycol and polypropylene glycol.

[0068] The polyol component may include 50 parts by weight or more, 55 parts by weight or more, 60 parts by weight or more, 65 parts by weight or more, 70 parts by weight or more, 75 parts by weight or more, or 80 parts by weight or more of polyether polyol relative to 100 parts by weight of polyester polyol, and in other examples, may include 120 parts by weight or less, 115 parts by weight or less, 110 parts by weight or less, 105 parts by weight or less, 100 parts by weight or less, or 90 parts by weight or less of said polyether polyol relative to 100 parts by weight of polyester polyol.

[0070] The subject part of the resin composition according to the present application may further include an alcohol compound and / or a thiol compound.

[0071] The subject part of the resin composition according to the present application includes an alcohol compound or a thiol compound in addition to the polyol component, thereby enabling the securing of a resin composition that forms a cured product having the desired appropriate elasticity and tensile strength.

[0072] At this time, elasticity and tensile strength can be expressed as a radius of curvature, and appropriate elasticity and tensile strength may mean a case where a curved surface with a radius of curvature of about 10 mm or less can be formed for a cured sample made using the resin composition with a width of 1 cm, a length of 10 cm, and a height of 2 mm. In other examples, the radius of curvature may be less than 9 mm, less than 8 mm, less than 7 mm, less than 6 mm, less than 5 mm, or less than 4 mm.

[0073] Alcohol compounds are compounds containing one hydroxyl group, and thiol compounds are compounds containing one thiol group.

[0074] The alcohol compound according to the present application may be represented by the following chemical formula 3, for example.

[0075] [Chemical Formula 3]

[0076]

[0077] In the above chemical formula 3, R1 is a single bond, an alkylene group, an alkenylene group, or an alkynylene group, and R2, R3, and R4 may each independently be hydrogen, an alkyl group, an alkenyl group, or an alkynylene group. In addition, in the above chemical formula 2, the sum of the number of carbon atoms present in R2, R3, and R4 may be in the range of 1 to 12, 2 to 10, 3 to 9, or 4 to 8.

[0078] In addition, in Chemical Formula 3, considering appropriate elasticity, R1 may be a single bond or an alkylene group, and R2, R3, and R4 may each independently be hydrogen or an alkyl group. Also, in this case, the sum of the number of carbon atoms present in R2, R3, and R4 may be within the range of 1 to 12, 2 to 10, 3 to 9, or 4 to 8.

[0079] The thiol compound according to the present application can be represented by the following chemical formula 4, for example.

[0080] [Chemical Formula 4]

[0081]

[0082] In the above chemical formula 4, R5 is a single bond, an alkylene group, an alkenylene group, or an alkynylene group, and R6, R7, and R8 may each independently be hydrogen, an alkyl group, an alkenyl group, or an alkynylene group. In addition, in the above chemical formula 3, the sum of the number of carbon atoms present in R6, R7, and R8 may be in the range of 1 to 12, 2 to 10, 3 to 9, or 4 to 8.

[0083] In addition, in Chemical Formula 4, considering appropriate elasticity, R5 may be a single bond or an alkylene group, and R6, R7, and R8 may each independently be hydrogen or an alkyl group. Also, in this case, the sum of the number of carbon atoms present in R6, R7, and R8 may be within the range of 1 to 12, 2 to 10, 3 to 9, or 4 to 8.

[0084] Alcohol compounds may be exemplified by ethanol, propanol, butanol, pentanol, hexanol, heptanol, octanol, 2-ethylhexanol, nonanol, decanol, 2-propylheptanol, ethenol, protenol, butenol, acetylenol, propineol, butinol, phenol, methylphenol, pyridinol, and methylpyridinol, but are not particularly limited as long as they contain one hydroxyl group. Additionally, one or more types of alcohol compounds may be used.

[0085] Thiol compounds may be exemplified by ethanethiol, propanethiol, butanethiol, pentanthiol, hexanethiol, heptanethiol, octanethiol, 2-ethylhexanethiol, nonanthiol, decanethiol, 2-propylheptanethiol, ethenethiol, protenethiol, butenethiol, acetylenethiol, propinethiol, butenethiol, benzenethiol, methylbenzenethiol, pyridinethiol, and methylpyridinethiol, but are not particularly limited as long as they contain one thiol group. Additionally, one or more types of thiol compounds may be used.

[0086] The content of the alcohol compound or thiol compound may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, or 30 parts by weight or more relative to 100 parts by weight of polyester polyol, and in other examples, may be 60 parts by weight or less, 55 parts by weight or less, 50 parts by weight or less, 45 parts by weight or less, or 40 parts by weight or less relative to 100 parts by weight of polyester polyol. When the content of the alcohol compound or thiol compound satisfies the above range, appropriate viscosity can be secured before and after curing to improve workability.

[0088] The subject part of the resin composition according to the present application may further include a filler. The filler may be a thermally conductive filler, and the thermally conductive filler is a filler capable of forming a cured product with thermal conductivity as described above.

[0089] The thermal conductivity of the thermally conductive filler itself may be, for example, about 1 W / m·K or more, about 5 W / m·K or more, about 10 W / m·K or more, or about 15 W / m·K or more. In another example, the thermal conductivity of the thermally conductive filler itself may be, for example, about 400 W / m·K or less, about 350 W / m·K or less, or about 300 W / m·K or less.

[0090] Thermally conductive fillers may include, for example, oxides such as aluminum oxide (alumina), magnesium oxide, beryllium oxide, or titanium oxide; nitrides such as boron nitride, silicon nitride, or aluminum nitride; carbides such as silicon carbide; hydrated metals such as aluminum hydroxide or magnesium hydroxide; metal fillers such as copper, silver, iron, aluminum, or nickel; metal alloy fillers such as titanium; silicon powder such as quartz, glass, or silica, but are not limited thereto.

[0091] In addition, if insulation properties can be ensured, the application of carbon fillers such as graphite may also be considered. For example, activated carbon can be used as the carbon filler. The form or proportion of the filler included in the cured material is not particularly limited and can be selected by considering the viscosity of the curable composition, the possibility of settling within the cured material, the desired thermal resistance or thermal conductivity, insulation properties, filling effect, or dispersibility.

[0092] The shape of the thermally conductive filler may be spherical and / or non-spherical (e.g., needle-shaped and plate-shaped, etc.) as appropriately selected as needed, but is not limited thereto.

[0093] One or more types of thermally conductive fillers may be used, appropriately selected as needed. In addition, even when using the same type of thermally conductive filler, those with different shapes may be mixed and those with different average particle sizes may be mixed and used. For example, aluminum hydroxide, aluminum, and alumina may be mixed and used as thermally conductive fillers, and their shapes and average particle sizes may differ from each other.

[0094] Generally, as the size of the thermally conductive filler decreases, the viscosity of the curable composition increases, and the likelihood of the thermally conductive filler settling within the cured product of the curable composition increases. In addition, as the size of the filler increases, the thermal resistance tends to increase. Therefore, considering the above points, an appropriate type of filler can be selected, and if necessary, two or more types of fillers may be used.

[0095] In addition, while it is advantageous to use spherical thermally conductive fillers considering the amount to be filled, thermally conductive fillers of shapes such as needle-shaped or plate-shaped can also be used considering the formation of the network or conductivity.

[0096] In one example, the curable composition may include a thermally conductive filler having an average particle size in the range of 0.001 μm to 80 μm. In another example, the average particle size of the thermally conductive filler may be 0.01 μm or more, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, or about 6 μm or more. In another example, the average particle size of the thermally conductive filler may be about 75 μm or less, about 70 μm or less, about 65 μm or less, about 60 μm or less, about 55 μm or less, about 50 μm or less, about 45 μm or less, about 40 μm or less, about 35 μm or less, about 30 μm or less, about 25 μm or less, about 20 μm or less, about 15 μm or less, about 10 μm or less, or about 5 μm or less.

[0097] In this case, the average particle size of the thermally conductive filler is the so-called D50 particle size (median particle size), which can refer to the particle diameter at 50% of the cumulative volume of the particle size distribution. That is, the particle size distribution is calculated based on volume, and the average particle size can be seen as the particle diameter at the point where the cumulative value reaches 50% on a cumulative curve where the total volume is set to 100%. Such a D50 particle size can be measured using the laser diffraction method.

[0098] Depending on the size of the thermally conductive filler, it can be classified into large thermally conductive fillers, medium thermally conductive fillers, and small thermally conductive fillers. Large thermally conductive fillers may have an average particle size of 80 μm or less, 78 μm or less, 76 μm or less, 74 μm or less, or 72 μm or less. In other examples, large thermally conductive fillers may have an average particle size of 60 μm or more, 62 μm or more, 64 μm or more, 66 μm or more, or 68 μm or more. Medium thermally conductive fillers may have an average particle size of 58 μm or less, 50 μm or less, 40 μm or less, or 25 μm or less. In other examples, medium thermally conductive fillers may have an average particle size of 10 μm or more, 12.5 μm or more, 15 μm or more, or 17.5 μm or more. The small thermally conductive filler may have an average particle size of 9 μm or less, 5 μm or less, or 3 μm or less. In other examples, the small thermally conductive filler may have an average particle size of 0.001 μm or more, 0.01 μm or more, 0.05 μm or more, 0.1 μm or more, 0.2 μm or more, 0.4 μm or more, 0.8 μm or more, or 1 μm or more.

[0099] Two or more of the large thermal conductive fillers, medium thermal conductive fillers, and small thermal conductive fillers may be selected and used. In this case, the thermal conductive fillers may satisfy the content ratio and / or particle size ratio, etc. within the following ranges to ensure room temperature rapid curing properties through appropriate combination with each component included in the curable composition of the present application.

[0100] When the thermally conductive filler includes large thermally conductive fillers, the content of the large thermally conductive fillers may be 30 wt% or more, 37.5 wt% or more, 42.5 wt% or more, 47.5 wt% or more, 50 wt% or more, 52.5 wt% or more, 55 wt% or more, or 57.5 wt% or more relative to the total weight of the thermally conductive fillers. In another example, the content of the large thermally conductive fillers may be 87.5 wt% or less, 80 wt% or less, 75 wt% or less, 72.5 wt% or less, 70 wt% or less, 67.5 wt% or less, 65 wt% or less, or 62.5 wt% or less relative to the total weight of the thermally conductive fillers. Additionally, it is preferable that the large thermally conductive fillers are spherical particles.

[0101] When the thermally conductive filler includes a medium-sized thermally conductive filler, the content of the medium-sized thermally conductive filler may be 5 wt% or more, 10 wt% or more, 12 wt% or more, 14 wt% or more, 16 wt% or more, 18 wt% or more, or 20 wt% or more relative to the total weight of the thermally conductive filler. In another example, the content of the medium-sized thermally conductive filler may be 52.5 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 36 wt% or less, 32 wt% or less, 28 wt% or less, 24 wt% or less, or 20 wt% or less relative to the total weight of the thermally conductive filler. Additionally, it is preferable that the medium-sized thermally conductive filler be spherical particles.

[0102] When the thermally conductive filler includes small thermally conductive fillers, the content of the small thermally conductive fillers may be 5 wt% or more, 10 wt% or more, 12 wt% or more, 14 wt% or more, 16 wt% or more, 18 wt% or more, or 20 wt% or more relative to the total weight of the thermally conductive fillers. In another example, the content of the small thermally conductive fillers may be 52.5 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 36 wt% or less, 32 wt% or less, 28 wt% or less, 24 wt% or less, or 20 wt% or less relative to the total weight of the thermally conductive fillers. Additionally, it is preferable that the small thermally conductive fillers are non-spherical (e.g., angular) particles.

[0103] When the thermally conductive filler comprises a large thermally conductive filler and a medium thermally conductive filler, considering the room temperature rapid curing properties of the curable composition according to the present application, it is preferable that the content of the medium thermally conductive filler be 25 parts by weight or more, 26 parts by weight or more, 27 parts by weight or more, 28 parts by weight or more, 29 parts by weight or more, or 30 parts by weight or more relative to 100 parts by weight of the large thermally conductive filler. In another example, considering the room temperature rapid curing properties of the curable composition according to the present application, it is preferable that the content of the medium thermally conductive filler be 45 parts by weight or less, 42.5 parts by weight or less, 40 parts by weight or less, 37.5 parts by weight or less, or 35 parts by weight or less relative to 100 parts by weight of the large thermally conductive filler. In addition, the value of the average particle size (D1) of the large thermal conductive filler / the average particle size (D2) of the medium thermal conductive filler is preferably 2 or more, 2.25 or more, 2.5 or more, 2.75 or more, 3 or more, 3.25 or more, or 3.5 or more, and preferably 5 or less, 4.5 or less, 4.25 or less, 4 or less, 3.75 or less, or 3.5 or less. When the large and medium thermal conductive fillers satisfy the above ranges, the room temperature rapid curing property of the curable composition according to the present application can be secured.

[0104] When the thermally conductive filler comprises large thermally conductive fillers and small thermally conductive fillers, considering the room temperature rapid curing properties of the curable composition according to the present application, it is preferable that the content of the small thermally conductive filler be 25 parts by weight or more, 26 parts by weight or more, 27 parts by weight or more, 28 parts by weight or more, 29 parts by weight or more, or 30 parts by weight or more relative to 100 parts by weight of the large thermally conductive filler. In another example, considering the room temperature rapid curing properties of the curable composition according to the present application, it is preferable that the content of the small thermally conductive filler be 45 parts by weight or less, 42.5 parts by weight or less, 40 parts by weight or less, 37.5 parts by weight or less, or 35 parts by weight or less relative to 100 parts by weight of the large thermally conductive filler. In addition, the value of the average particle size (D1) of the large thermal conductive filler / the average particle size (D3) of the small thermal conductive filler is preferably 10 or more, 15 or more, 20 or more, 25 or more, 30 or more, or 32.5 or more, and preferably 500 or less, 100 or less, 90 or less, 80 or less, 70 or less, 60 or less, or 50 or less. When the large and small thermal conductive fillers satisfy the above ranges, the room temperature rapid curing property of the curable composition according to the present application can be secured.

[0105] In this application, it is most preferable to use a thermally conductive filler comprising large, medium, and small thermally conductive fillers. In this case, the content ratio and average particle size ratio of each particle are as described above, and the room-temperature rapid curing property of the curable composition according to this application can be secured through the binder component and an appropriate combination thereof.

[0106] The thermally conductive filler may include spherical and non-spherical particles. In this application, the term "spherical particle" refers to a particle with a sphericity of about 0.95 or higher, and "non-spherical particle" refers to a particle with a sphericity of less than 0.95. The sphericity can be verified through particle shape analysis. Specifically, the sphericity of a three-dimensional particle filler can be defined as the ratio (S' / S) of the surface area (S) of the particle and the surface area (S') of a sphere having the same volume as the particle. For actual particles, circularity is generally used. The circularity is expressed as the ratio of the boundary (P) of a circle having the same area (A) as the image to the boundary of a two-dimensional image of the actual particle, and is calculated using the following formula.

[0107] <Circular Diagram Formula>

[0108] Circularity = 4πA / P 2

[0109] The above sphericity is represented by a value from 0 to 1, where a perfect circle has a value of 1, and particles of irregular shape have a value lower than 1. The sphericity value in this specification is the average value of the sphericity measured by Marvern's particle shape analysis equipment (FPIA-3000).

[0110] Considering the appropriate viscosity and thixotropy of the curable composition according to the present application, the content of non-spherical particles may be 10 parts by weight or more, 12.5 parts by weight or more, 15 parts by weight or more, 17.5 parts by weight or more, 20 parts by weight or more, or 22.5 parts by weight or more relative to 100 parts by weight of spherical particles, and in other examples, may be 45 parts by weight or less, 40 parts by weight or less, 35 parts by weight or less, or 30 parts by weight or less.

[0111] To obtain excellent heat dissipation performance, it may be considered to use a high amount of thermally conductive filler. The content of the filler in the main part may be 300 parts by weight or more, 400 parts by weight or more, 500 parts by weight or more, 600 parts by weight or more, 700 parts by weight or more, 800 parts by weight or more, 900 parts by weight or more, or 1,000 parts by weight or more, relative to 100 parts by weight of the polyol component. In another example, the content of the filler may be 2,000 parts by weight or less, 1,800 parts by weight or less, 1,600 parts by weight or less, 1,400 parts by weight or less, or 1,200 parts by weight or less, relative to 100 parts by weight of the polyol component.

[0113] 2. Hardener Part

[0114] The resin composition according to the present application comprises a curing agent part having an isocyanate component. The isocyanate component of the curing agent part may include a difunctional isocyanate compound and a polyfunctional isocyanate compound with three or more functions.

[0115] In this case, a polyfunctional isocyanate compound refers to a compound containing three or more isocyanate groups. Additionally, the polyfunctional isocyanate compound is suitable as a trifunctional isocyanate compound containing three isocyanate groups.

[0116] The curing agent part of the resin composition according to the present application can secure a resin composition that forms a cured product having desired hardness, adhesion, and reworkability by simultaneously including a difunctional isocyanate compound and a polyfunctional isocyanate compound. Specifically, if the difunctional isocyanate compound is not included, the hardness increases, causing the resin composition to become brittle and have low flexibility after curing. Furthermore, if the polyfunctional isocyanate compound is not included, the adhesion increases, making it difficult to secure the desired reworkability.

[0117] The types of difunctional isocyanate compounds and polyfunctional isocyanate compounds are not particularly limited. However, to secure the desired physical properties, non-aromatic isocyanate compounds that do not contain aromatic groups may be used. That is, it may be advantageous to use aliphatic or alicyclic series. If aromatic polyisocyanates are used, the reaction rate may be excessively fast and the glass transition temperature of the cured product may be high, making it difficult to secure processability and physical properties suitable for the intended use of the composition of the present application.

[0118] As the difunctional isocyanate compound according to the present application, at least one of an aliphatic difunctional isocyanate compound and alicyclic difunctional isocyanate compound may be used. Aliphatic difunctional isocyanate compounds may be exemplified by hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, norbornane diisocyanate methyl, ethylene diisocyanate, propylene diisocyanate, and tetramethylene diisocyanate, but are not particularly limited thereto. Alicyclic difunctional isocyanate compounds may be exemplified by transcyclohexane-1,4-diisocyanate, isophorone diisocyanate, bis(isocyanatemethyl)cyclohexane diisocyanate, and dicyclohexylmethane diisocyanate, but are not particularly limited thereto. In addition, one or more types of difunctional isocyanate compounds may be used.

[0119] The polyfunctional isocyanate compound according to the present application is not particularly limited as long as it is a compound containing three or more isocyanate groups. For example, the polyfunctional isocyanate compound according to the present application may use a trimer or higher polymer of an isocyanate compound, and may also use a biuret-type compound obtained by reacting an isocyanate compound with water. That is, at least one selected from a polymer of an isocyanate compound and a biuret compound may be used as the polyfunctional isocyanate compound.

[0120] Specifically, examples of polyfunctional isocyanate compounds include polymers and biuret-type compounds such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, norbornane diisocyanate methyl, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, transcyclohexane-1,4-diisocyanate, isophorone diisocyanate, bis(isocyanatemethyl)cyclohexane diisocyanate, and dicyclohexylmethane diisocyanate.

[0121] The content of the polyfunctional isocyanate compound may be 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, 50 wt% or more, 55 wt% or more, or 60 wt% or more relative to the total weight of the isocyanate component, and in another example, the content of the polyfunctional isocyanate compound may be 85 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, or 65 wt% or less relative to the total weight of the isocyanate component.

[0122] The content of the difunctional isocyanate compound may be 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 35 parts by weight or more, 40 parts by weight or more, 45 parts by weight or more, 50 parts by weight or more, or 55 parts by weight or more, relative to 100 parts by weight of the polyfunctional isocyanate compound. In another example, the content of the difunctional isocyanate compound may be 95 parts by weight or less, 90 parts by weight or less, 85 parts by weight or less, 80 parts by weight or less, 75 parts by weight or less, 70 parts by weight or less, or 65 parts by weight or less, relative to 100 parts by weight of the polyfunctional isocyanate compound.

[0123] When the content of the polyfunctional isocyanate compound and the content of the difunctional isocyanate compound each satisfy the above ranges, a resin composition that forms a cured product having reworkability and flexibility can be obtained.

[0124] In order to obtain excellent heat dissipation performance, it may be considered to use a high amount of thermally conductive filler. The content of the filler in the curing agent part may be 500 parts by weight or more, 600 parts by weight or more, 700 parts by weight or more, 800 parts by weight or more, 900 parts by weight or more, 1,000 parts by weight or more, 1,100 parts by weight or more, 1,200 parts by weight or more, 1,300 parts by weight or more, 1,400 parts by weight or more, 1,500 parts by weight or more, 1,600 parts by weight or more, 1,700 parts by weight or more, or 1,800 parts by weight or more, relative to 100 parts by weight of the isocyanate component. In another example, the content of the filler may be 3,000 parts by weight or less, 2,800 parts by weight or less, 2,600 parts by weight or less, 2,400 parts by weight or less, 2,200 parts by weight or less, or 2,100 parts by weight or less relative to 100 parts by weight of the isocyanate component.

[0125] In addition, the filler used in the hardener part may have the same characteristics as the filler described in the subject part, except for the content ratio.

[0127] 3. Resin composition and cured product thereof

[0128] As described above, the resin composition according to the present application may be a one-component or two-component composition.

[0129] In the resin composition according to the present application, the ratio (V1 / V2) of the volume of the main part (V1) to the volume of the curing agent part (V2) may be within the range of 0.5 to 1.5 or 0.75 to 1.25. When the ratio (V1 / V2) of the volume of the main part (V1) to the volume of the curing agent part (V2) satisfies the above range, the urethane reaction can be carried out efficiently.

[0130] In the resin composition according to the present application, the main component part and the curing agent part may be physically separated.

[0131] The resin composition of the present application may include an excess amount of filler to ensure heat dissipation (thermal conductivity) or to ensure thixotropy as required for the process. If an excess amount of filler is used, the viscosity of the composition increases, which may impair processability when injecting the composition into the case of a battery module. Therefore, even while including an excess amount of filler, sufficient low viscosity characteristics are required so as not to hinder processability. Furthermore, since simply exhibiting low viscosity makes it difficult to ensure processability, appropriate thixotropy is required, and it may be necessary to exhibit the desired appropriate adhesion upon curing, and for the curing itself to proceed at room temperature.

[0132] In the resin composition according to the present application, when mixing the main component part and the curing agent part, the content of the filler may be 75 wt% or more, 76 wt% or more, 77 wt% or more, 78 wt% or more, 79 wt% or more, 80 wt% or more, 81 wt% or more, 82 wt% or more, 83 wt% or more, 84 wt% or more, 85 wt% or more, 86 wt% or more, 87 wt% or more, or 88 wt% or more relative to the total weight of the mixture. In another example, the content of the filler may be 96 wt% or less, 95 wt% or less, 94 wt% or less, 93 wt% or less, 92 wt% or less, 91 wt% or less, 90 wt% or less, or 89 wt% or less relative to the total weight of the mixture.

[0134] The resin composition according to the present application may additionally include a plasticizer if necessary. The plasticizer is an additive that reduces the viscosity or plasticity of a material and may include phthalate-based, trimellit-based, epoxy-based, polyester-based plasticizers, etc. Phthalate-based plasticizers include, for example, DEHP (Diethylhexyl phthalate), DINP (Diisononyl phthalate), DIDP (Diisodecyl phthalate), etc. Trimelt-based plasticizers include, for example, TOTM (Tris (2-Ethylhexyl) Trimellitate), etc. In addition, epoxy-based plasticizers include, for example, epoxidized soybean oil (ESBO), etc. Furthermore, in addition to those described above, the plasticizer may be polyvinyl acetate used as an emulsion for general-purpose adhesives, etc., but is not limited thereto.

[0135] The resin composition according to the present application may additionally include a viscosity modifier, such as a thixotropic agent, a diluent, a dispersant, a surface treatment agent, or a coupling agent, if necessary, to control viscosity, for example, to increase or decrease viscosity, or to control viscosity according to shear force. The thixotropic agent can control the viscosity of the resin composition according to shear force. Examples of thixotropic agents that can be used include fumed silica. Diluents or dispersants are typically used to lower the viscosity of the resin composition, and any various types known in the industry that can exhibit such an action may be used without limitation. Surface treatment agents are for surface treatment of fillers introduced into the cured product of the resin composition, and any various types known in the industry that can exhibit such an action may be used without limitation. In the case of coupling agents, for example, they may be used to improve the dispersibility of thermally conductive fillers such as alumina, and any various types known in the industry that can exhibit such an action may be used without limitation.

[0136] The resin composition according to the present application may additionally include a flame retardant or a flame retardant adjuvant, etc., if necessary. A resin composition additionally including a flame retardant or a flame retardant adjuvant, etc., can be cured to form a flame-retardant resin. In the present application, the term flame-retardant resin may refer to a resin that exhibits a V-0 rating in the UL 94V Test (Vertical Burning Test). Various known flame retardants may be applied as flame retardants without special limitations; for example, solid filler-type flame retardants or liquid flame retardants may be applied. Examples of flame retardants include organic flame retardants such as melamine cyanurate or inorganic flame retardants such as magnesium hydroxide, but are not limited thereto. When the amount of thermally conductive filler included in the resin composition is large, liquid-type flame retardant materials (TEP, Triethyl phosphate or TCPP, tris(1,3-chloro-2-propyl)phosphate, etc.) may also be used. In addition, a silane coupling agent capable of acting as a flame retardant enhancer may be added.

[0137] The above composition may include the configuration described above and may be a solvent-based composition, a water-based composition, or a solvent-free composition; however, considering the convenience of the manufacturing process described below, a solvent-free composition may be appropriate.

[0139] A resin composition can be cured to form a cured product and may have at least one of the following properties. Each of the following properties is independent, and no single property takes precedence over another; the cured product of the resin composition may satisfy at least one or two of the following properties. The cured product of the resin composition satisfying at least one or two of the following properties is attributed to the combination of each component of the resin composition.

[0140] The cured product of the resin composition may have a thermal resistance of about 5 kW or less, about 4.5 kW or less, about 4 kW or less, about 3.5 kW or less, about 3 kW or less, or about 2.8 kW or less. When controlled to achieve a thermal resistance within this range, excellent cooling efficiency or heat dissipation efficiency can be secured. The above thermal resistance may be a value measured according to ASTM D5470 or ISO 22007-2 standards, and the method of measurement is not particularly limited.

[0141] The cured product of the resin composition has an adhesion strength to aluminum of approximately 0.1 N / mm 2 Less than, approximately 0.09 N / mm 2 Less than, approximately 0.08 N / mm 2 Less than, approximately 0.07 N / mm 2 Less than or about 0.06 N / mm 2 It may be less. In another example, the cured product of the resin composition has an adhesive strength of about 0.01 N / mm 2 Above, approximately 0.02 N / mm 2 Above, approximately 0.03 N / mm 2 Above, approximately 0.04 N / mm 2 Greater than or about 0.05 N / mm 2 It could be more than that.

[0142] The above adhesive strength may be a value obtained by applying the resin composition to an aluminum substrate with a width of 2 cm, a length of 2 cm, and a thickness of 2 mm, maintaining it for 24 hours to cure it, and then measuring the cured product using a Texture Analyzer (TA) at a peeling speed of 0.5 mm / s and a peeling angle of 90 degrees.

[0143] Furthermore, the adhesive force may be the adhesive force to any substrate or module case in contact with the cured material of the resin composition. If such an adhesive force can be secured, appropriate adhesive force can be exhibited to various materials, such as cases or battery cells included in a battery module. Moreover, if an adhesive force within this range is secured, delamination caused by volume changes during the charging and discharging of battery cells in the battery module, changes in the operating temperature of the battery module, or curing shrinkage can be prevented, thereby ensuring excellent durability. Additionally, reworkability can be secured, allowing for the separation and reattachment of the module during the assembly process of the battery pack.

[0144] A cured product of the resin composition can be produced with a width of 1 cm, a length of 10 cm, and a height of 2 mm to form a curved surface with a radius of curvature of about 10 mm or less. In other examples, the radius of curvature may be less than 9 mm, less than 8 mm, less than 7 mm, less than 6 mm, less than 5 mm, or less than 4 mm.

[0145] The cured product of the resin composition can ensure durability for application to products requiring a long warranty period (approximately 15 years or more in the case of automobiles), such as automobiles. Durability may mean that after a thermal shock test in which a cycle is repeated 100 times, with the temperature being maintained at a low temperature of approximately -40°C for 30 minutes and then raised to 80°C and maintained for 30 minutes, the product does not detach, peel, or crack from the module case or battery cell of the battery module.

[0146] The cured product of the resin composition may have electrical insulation properties of about 3 kV / mm or more, about 5 kV / mm or more, about 7 kV / mm or more, 10 kV / mm or more, 15 kV / mm or more, or 20 kV / mm or more. The higher the value of the dielectric breakdown voltage, the better the insulation properties of the cured product of the resin composition; the above values ​​may be about 50 kV / mm or less, 45 kV / mm or less, 40 kV / mm or less, 35 kV / mm or less, or 30 kV / mm or less, but are not particularly limited. To achieve such dielectric breakdown voltages, an insulating filler may be applied to the resin composition. Generally, among thermally conductive fillers, ceramic fillers are known as components capable of ensuring insulation properties. The above electrical insulation properties may be measured by the dielectric breakdown voltage measured according to ASTM D149 standards. In addition, if the cured product of the resin composition can secure electrical insulation properties as described above, it is possible to ensure stability while maintaining performance for various materials, such as cases or battery cells included in battery modules.

[0147] The cured product of the resin composition may have a specific gravity of 5 or less. In other examples, the specific gravity may be 4.5 or less, 4 or less, 3.5 or less, or 3 or less. Since a lower specific gravity value of the cured product of the resin composition is advantageous for lightweighting the application product, the lower limit thereof is not specifically restricted. For example, the specific gravity may be about 1.5 or more or 2 or more. In order for the cured product of the resin composition to exhibit a specific gravity within the above range, for example, when adding a thermally conductive filler, methods such as applying a filler that can secure the desired thermal conductivity even at a low specific gravity, i.e., applying a filler with inherently low specific gravity or applying a surface-treated filler may be used.

[0148] It is appropriate for the cured product of the resin composition not to contain volatile substances as much as possible. For example, the cured product of the resin composition may have a non-volatile component ratio of 90% by weight or more, 95% by weight or more, or 98% by weight or more. The ratio with respect to the non-volatile component may be defined in the following manner. That is, the non-volatile component may be defined as the portion remaining after maintaining the cured product of the resin composition at 100°C for about 1 hour, and thus the ratio may be measured based on the ratio of the initial weight of the cured product of the resin composition to the weight after maintaining it at 100°C for about 1 hour.

[0149] The cured product of the resin composition will have excellent resistance to degradation as needed, and stability that is as chemically non-reactive as possible may be required.

[0150] It may be advantageous for the cured product of the resin composition to have a low shrinkage rate during the curing process or after curing. This prevents delamination or the formation of voids that may occur during the manufacturing or use of various materials, such as cases included in battery modules or battery cells. The shrinkage rate can be appropriately controlled within a range that exhibits the aforementioned effects, and may be, for example, less than 5%, less than 3%, or less than about 1%. Since a lower value of the shrinkage rate is advantageous, there is no specific lower limit.

[0151] It may also be advantageous for the cured product of the resin composition to have a low coefficient of thermal expansion (CTE). This prevents delamination or the formation of voids that may occur during the manufacturing or use of various materials, such as cases included in battery modules or battery cells. The coefficient of thermal expansion can be appropriately adjusted within a range that exhibits the aforementioned effects, and may be, for example, less than 300 ppm / K, less than 250 ppm / K, less than 200 ppm / K, less than 150 ppm / K, or less than 100 ppm / K. Since a lower value of the coefficient of thermal expansion is advantageous, its lower limit is not specifically restricted.

[0152] The cured product of the resin composition can have its tensile strength appropriately controlled, thereby ensuring excellent impact resistance. The tensile strength can be controlled, for example, in a range of about 1.0 MPa or higher.

[0153] The cured product of the resin composition can have its elongation appropriately controlled, thereby ensuring excellent impact resistance. The elongation can be controlled, for example, in a range of about 10% or more or about 15% or more.

[0154] It may also be advantageous for the cured product of the resin composition to exhibit appropriate hardness. The term "appropriate hardness" may refer to a hardness such that the cured product of the resin composition is not evaluated as brittle. If the hardness of the cured product of the resin composition is excessively high, the cured product of the resin composition may become excessively brittle, which may have a negative effect on reliability. Furthermore, by controlling the hardness, impact resistance and vibration resistance can be secured, and the durability of the product can be secured. The hardness of the cured product of the resin composition can be measured using a durometer. Additionally, the hardness of the cured product of the resin composition, for example, may be less than 85, less than 80, less than 75, less than 70, or less than 65 in the Shore 00 type after being produced as a sample with a width of 2 cm, a length of 2 cm, and a thickness of 0.5 to 1 cm, and in other examples, the hardness may be 40 or more, 45 or more, 50 or more, 55 or more, or 60 or more. The hardness of a cured product of a resin composition is typically determined by the type or ratio of filler included in the cured product, and if an excessive amount of filler is included, the hardness is typically higher.

[0155] The cured product of the resin composition may also have a 5% weight loss temperature in thermogravimetric analysis (TGA) of 400°C or higher, or an 800°C residual of 70% or higher. Due to these characteristics, the stability at high temperatures can be further improved for various materials, such as cases included in battery modules or battery cells. In other examples, the 800°C residual may be about 75% or higher, about 80% or higher, about 85% or higher, or about 90% or higher. In other examples, the 800°C residual may be about 99% or lower. The thermogravimetric analysis (TGA) is 60 cm 3Measurements can be taken within the range of 25°C to 800°C at a heating rate of 20°C / min under a nitrogen (N2) atmosphere of 20°C / min. The above thermogravimetric analysis (TGA) results can also be achieved by controlling the composition of the cured product of the resin composition. For example, the 800°C residual amount is determined by the type or ratio of thermally conductive fillers included in the cured product of the resin composition, and if an excess amount of thermally conductive fillers is included, the residual amount increases. However, if the polymer and / or monomer used in the resin composition generally has higher heat resistance than other polymers and / or monomers, the residual amount is even higher, and thus the polymer and / or monomer components included in the cured product of the resin composition also affect the hardness.

[0156] The resin composition of the present application may be formed by mixing each of the components listed above. Additionally, the resin composition may be formed by further adding a plasticizer, a flame retardant, a dispersant, etc., to the mixture formed by mixing above, and then mixing.

[0157] The resin composition of the present application is not particularly limited to the mixing order as long as all necessary components can be included.

[0158] The resin composition of the present application can dissipate heat generated when used in various electric and electronic products, such as irons, washing machines, dryers, garment care systems, electric shavers, microwave ovens, electric ovens, electric rice cookers, refrigerators, dishwashers, air conditioners, fans, humidifiers, air purifiers, mobile phones, walkie-talkies, televisions, radios, computers, and laptops, or in batteries such as secondary batteries. In particular, in battery vehicle batteries manufactured by assembling battery cells to form a single battery module and assembling multiple battery modules to form a single battery pack, the resin composition of the present application can be used as a material for connecting battery modules. When the resin composition of the present application is used as a material for connecting battery modules, it can serve to dissipate heat generated from the battery cells and to secure the battery cells against external shocks and vibrations.

[0159] The cured product of the resin composition of the present application can transfer heat generated from a heat-generating element to a cooling area. That is, the cured product of the resin composition can dissipate heat generated from the heat-generating element.

[0160] The cured product of the resin composition can be positioned between the heat-generating element and the cooling area to bring them into thermal contact. Thermal contact means that the cured product of the resin composition is in direct physical contact with the heat-generating element and the cooling area to dissipate heat generated from the heat-generating element to the cooling area, or that even if the cured product of the resin composition is not in direct contact with the heat-generating element and / or the cooling area (i.e., a separate layer exists between the cured product of the resin composition and the heat-generating element and / or the cooling area), the heat generated from the heat-generating element is dissipated to the cooling area. Effects of the invention

[0162] The present application may provide a resin composition exhibiting appropriate viscosity, thixotropy, and / or thermal conductivity before and after curing.

[0163] The present application may provide a resin composition that exhibits appropriate adhesion to effectively maintain multiple battery modules before and after curing, and at the same time, reworkability to enable the separation and reattachment of modules during the assembly process of a battery pack.

[0164] The present application can also provide a resin composition that exhibits room temperature curing and rapid curing properties even when containing an excess amount of filler. Specific details for implementing the invention

[0166] The present application is described below through examples and comparative examples, but the scope of the present application is not limited by the contents presented below.

[0168] Methods for Measuring Physical Properties

[0169] (1) Method for measuring the number average molecular weight of polymer compounds

[0170] Number average molecular weight (M) of a polymer compound n ) was measured using Gel Permeation Chromatography (GPC). The target polymer compound was placed in a 5 mL vial and diluted in Tetrahydrofuran (THF) to a concentration of approximately 1 mg / mL. Subsequently, the standard sample for calibration and the sample to be analyzed were filtered through a syringe filter (pore size: 0.45 µm) before measurement. The analysis program used was ChemStation by Agilent Technologies, and the number average molecular weight (M) was determined by comparing the elution time of the sample with the calibration curve. n ) was obtained.

[0171] Also, the symbol M mentioned in this specification n Unless otherwise specified, it refers to the number-average molecular weight.

[0172] <GPC 측정 조건>

[0173] Device: Agilent Technologies 1200 series

[0174] Column: Used 2 PLgel mixed B units from Polymer Laboratories

[0175] Solvent: THF

[0176] Column temperature: 35 ℃

[0177] Sample concentration: 1 mg / mL, 200 μL injection

[0178] Standard Sample: Polystyrene (Mp: 3900000, 723000, 316500, 52200, 31400, 7200, 3940, 485)

[0180] (2) Thermal conductivity evaluation method

[0181] Thermal conductivity was measured using the hot disk method. Specifically, thermal conductivity was measured according to ISO 22007-2 standards along the thickness direction of a circular sample in which the resin composition was cured with a diameter of 4 cm and a thickness of approximately 500 μm.

[0183] (3) Adhesion strength evaluation method

[0184] A resin composition was coated with a width of 2 cm, a length of 2 cm, and a thickness of 2 mm on an aluminum substrate (P substrate) measuring approximately 6 cm in width and 2 cm in length. An aluminum substrate (Q substrate) measuring approximately 6 cm in width and 2 cm in length was placed on the coated resin composition to cross the P substrate, forming a cross shape, and the resin composition was cured by maintaining it at room temperature for about 24 hours. Subsequently, the adhesion strength of the cured product to the aluminum substrate was measured by peeling the P substrate or Q substrate at a peeling speed of 0.5 mm / s and a peeling angle of 90 degrees using a Texture Analyzer (TA).

[0186] (4) Flame retardancy evaluation method

[0187] The resin composition was applied to a width of 13 mm, a length of 120 mm, and a thickness of 2 mm, and then cured by maintaining it at room temperature for 24 hours. Afterward, flame retardancy was evaluated according to the UL94 V Test (Vertical Burning Test).

[0189] (5) Hardness evaluation method

[0190] Hardness was evaluated using an ASKER durometer hardness instrument according to ASTM D 2240 and JIS K 6253 standards. The resin composition was coated in the shape of a square prism with a width of 2 cm, a length of 2 cm, and a thickness of 1 cm, and cured by maintaining it at room temperature for 24 hours. An initial hardness was measured by applying a load of 1 kg or more (approx. 1.5 kg) to the surface of the cured product, and the hardness was evaluated by confirming the stabilized measurement value after 15 seconds.

[0192] (6) Method for evaluating elasticity and tensile strength

[0193] Elasticity and tensile strength were evaluated by measuring the radius of curvature. A resin composition was coated to obtain a cured product with a width of 1 cm, a length of 10 cm, and a thickness of 2 mm, and cured by maintaining it at room temperature for 24 hours. The cured product was attached to a cylinder with various radii and bent, and the radius of curvature of the cylinder at which no cracks occurred in the cured product was evaluated. The smaller the radius of curvature, the more the cured product is evaluated to have appropriate elasticity and tensile strength.

[0195] Example 1

[0196] Trifunctional polyester polyol (F-2010, M n= 2,000 g / mol, Kuraray Co.), difunctional polyether polyol (PPG-1000D, Mn = 1,000 g / mol, Kumho Petrochemical Co.), 2-propylheptanol (2-PH), and filler (F) were mixed in a weight ratio of 100:85:35:1,931 (F-2010:PPG-1000D:2-PH:F) to prepare the main part (A1). At this time, the filler (F) is a mixture of angular alumina (F1) with an average particle size of about 2 μm, spherical alumina (F2) with an average particle size of about 20 μm, and spherical alumina (F3) with an average particle size of about 70 μm in a weight ratio of 20:20:60 (F1:F2:F3).

[0197] The average particle size of the filler mentioned in this specification is the D50 particle size, also known as the so-called median particle size, and is the particle diameter (median diameter) at 50% of the cumulative value of the cumulative curve of the particle size distribution based on volume. This particle size can be defined as the particle diameter at the point where the cumulative value reaches 50% on a cumulative curve where the total volume is 100%, obtained by calculating the particle size distribution based on volume. The above D50 particle size can be measured using a Marven MASTERSIZER 3000 instrument in accordance with ISO-13320, and ethanol was used as the solvent.

[0198] The curing agent part (A2) was prepared by mixing an HDI (hexamethylene diisocyanate)-based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex), an HDI (hexamethylene diisocyanate)-based difunctional isocyanate compound (AE700-100, Asahi Kasei), and a filler (F) in a weight ratio of 100:60:2,974 (HDB-LV:AE700-100:F).

[0199] Upon curing, the above main part (density: approximately 2.5 g / cm³) 3 ) and hardener part (density: approx. 3.1 g / cm³ 3) was mixed in a volume ratio of approximately 1:1 (A1:A2) and then cured.

[0200] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0202] Example 2

[0203] The main component and the curing agent part were prepared in the same manner as in Example 1, except that an HDI (hexamethylene diisocyanate) based trimer compound (TLA-100, trifunctional, Asahi Kasei) was used instead of an HDI (hexamethylene diisocyanate) based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex) when preparing the curing agent part.

[0204] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0206] Comparative Example 1

[0207] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n The main component and the curing agent part were prepared in the same manner as in Example 1, except that 2-propylheptanol (2-PH) and 2-functional polyester polyol (P-1010, Mn = 1,000 g / mol, Kumho Petrochemical), 2-ethylhexanol (2-EH), and filler (F) were mixed in a weight ratio of 100:30:1,269 (P-1010:2-EH:F) and used, without using 2-propylheptanol (2-PH).

[0208] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0210] Comparative Example 2

[0211] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n The main component and curing agent parts were prepared in the same manner as in Example 1, except that 2-propylheptanol (2-PH) and 2-functional polyester polyol (P-1010, Mn = 1,000 g / mol, Kumho Petrochemical), 2-ethylhexanol (2-EH), and filler (F) were mixed in a weight ratio of 100:50:1,484 (P-1010:2-EH:F) and used, without using 2-propylheptanol (2-PH).

[0212] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0214] Comparative Example 3

[0215] In the manufacture of the main part, instead of using difunctional polyether polyol (PPG-1000D, Mn= 1,000 g / mol, Kumho Petrochemical Co.) and 2-propylheptanol (2-PH), trifunctional polyester polyol (F-2010, M n The main component and the curing agent part were prepared in the same manner as in Example 1, except that 2-ethylhexanol (2-EH) and a filler (F) were mixed in a weight ratio of 100:50:1,518 (F-2010:2-EH:F) and used.

[0216] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0218] Comparative Example 4

[0219] When manufacturing the subject part, 2-propylheptanol (2-PH) is not used, and a trifunctional polyester polyol (F-2010, M) is used. n The main component and the curing agent part were prepared in the same manner as in Example 1 above, except that a difunctional polyether polyol (PPG-1000D, Mn = 2,000 g / mol, Kuraray Co.), a difunctional polyether polyol (PPG-1000D, Mn = 1,000 g / mol, Kumho Petrochemical Co.), and a filler (F) were mixed in a weight ratio of 100:500:4,400 (F-2010:PPG-1000D:F).

[0220] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0222] Comparative Example 5

[0223] The main component and the curing agent part were prepared in the same manner as in Example 1, except that 2-ethylhexanol (2-EH) was used instead of 2-propylheptanol (2-PH) when preparing the main component part, and when preparing the curing agent part, an HDI (hexamethylene diisocyanate) based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex) was not used, but an HDI (hexamethylene diisocyanate) based difunctional isocyanate compound (AE700-100, Asahi Kasei) and a filler (F) were mixed in a weight ratio of 100:1,420 (AE700-100:F) instead.

[0224] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0226] Comparative Example 6

[0227] The main component and the curing agent part were prepared in the same manner as in Example 1, except that a difunctional isocyanate compound (AE700-100, Asahi Kasei) was not used when preparing the curing agent part, and an HDI (hexamethylene diisocyanate)-based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex) and a filler (F) were mixed in a weight ratio of 100:2,569 (HDB-LV:F).

[0228] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0230] Comparative Example 7

[0231] When manufacturing the subject part, 2-propylheptanol (2-PH) is not used, and a trifunctional polyester polyol (F-2010, M) is used. n = 2,000 g / mol, Kuraray), difunctional polyether polyol (PPG-1000D, Mn= 1,000 g / mol, Kumho Petrochemical), and filler (F) are mixed and used in a weight ratio of 100:100:1,411 (F-2010: PPG-2000D:F), and

[0232] The main component and the curing agent part were prepared in the same manner as in Example 1, except that when preparing the curing agent part, an HDI (hexamethylene diisocyanate)-based isocyanate biprotic compound (AE700-100, Asahi Kasei) and a filler (F) were mixed in a weight ratio of 100:2,036 (AE700-100:F) instead of using an HDI (hexamethylene diisocyanate)-based isocyanate biprotic compound (AE700-100, Asahi Kasei) and used.

[0233] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0235] Comparative Example 8

[0236] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n = 2,000 g / mol, Kuraray) and 2-propylheptanol (2-PH) are not used, and a trifunctional polyether polyol (PPG-1000, Mn= 1,000 g / mol, Kumho Petrochemical), a difunctional polyether polyol (PPG-1000D, Mn= 1,000 g / mol, Kumho Petrochemical), and a filler (F) are mixed and used in a weight ratio of 100:100:2,274 (PPG-1000:PPG-1000D:F).

[0237] The main component and the curing agent part were prepared in the same manner as in Example 1, except that when preparing the curing agent part, an HDI (hexamethylene diisocyanate)-based isocyanate bifunctional compound (AE700-100, Asahi Kasei) and a filler (F) were mixed in a weight ratio of 100:1,485 (AE700-100:F) instead of using an HDI (hexamethylene diisocyanate)-based isocyanate bifunctional compound (AE700-100, Asahi Kasei) and used.

[0238] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0240] Comparative Example 9

[0241] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n The main component and the curing agent part were prepared in the same manner as in Example 1 above, except that 2-propylheptanol (2-PH) and 2-functional polyether polyol (PPG-1000D, Mn = 1,000 g / mol, Kumho Petrochemical Co.) and filler (F) were mixed in a weight ratio of 100:802 (P-1010:F) instead of using 2-propylheptanol (2-PH).

[0242] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0244] Comparative Example 10

[0245] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n= 2,000 g / mol, Kuraray) and 2-propylheptanol (2-PH) are not used, and a difunctional polyether polyol (PPG-1000D, Mn= 1,000 g / mol, Kumho Petrochemical), 2-ethylhexanol (2-EH), and a filler (F) are mixed in a weight ratio of 100:40:1,119 (P-1010:2-EH:F) and used,

[0246] The main component and the curing agent part were prepared in the same manner as in Example 1, except that when preparing the curing agent part, an HDI (hexamethylene diisocyanate)-based difunctional isocyanate compound (AE700-100, Asahi Kasei) was not used, and an HDI (hexamethylene diisocyanate)-based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex) and a filler (F) were mixed in a weight ratio of 100:1,676 (HDB-LV:F).

[0247] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0249] Comparative Example 11

[0250] During the manufacture of the subject part, trifunctional polyester polyol (F-2010, M n = 2,000 g / mol, Kuraray) and 2-propylheptanol (2-PH) are not used, and a difunctional polyether polyol (PPG-1000D, Mn = 1,000 g / mol, Kumho Petrochemical) and a filler (F) are mixed in a weight ratio of 100:745 (PPG-1000D:F) and used, and

[0251] The main component and the curing agent part were prepared in the same manner as in Example 1, except that when preparing the curing agent part, an HDI (hexamethylene diisocyanate)-based difunctional isocyanate compound (AE700-100, Asahi Kasei) was not used, and an HDI (hexamethylene diisocyanate)-based isocyanate biuret compound (HDB-LV, trifunctional, Vencorex) and a filler (F) were mixed in a weight ratio of 100:2,497 (HDB-LV:F).

[0252] The above-mentioned main component and hardener part were poured into a mold in a volume ratio of approximately 1:1 and maintained at room temperature for 24 hours to form a disk-shaped cured product having a diameter of 4 cm and a thickness of 500 μm.

[0254] The results of the physical property measurements of the above examples and comparative examples are shown in the table below.

[0255] division Thermal conductivity (W / mK) flame retardant Adhesion (N / mm) 2 ) Hardness (Shore 00) Radius of curvature (mm) Example 1 > 2.5 V-0 0.05 60 3 Example 2 0.08 70 2.5 Comparative Example 1 0.05 91 3 Comparative Example 2 0.13 56 2.5 Comparative Example 3 0.18 55 3 Comparative Example 4 0.13 97 >10 Comparative Example 5 0.30 76 4 Comparative Example 6 0.15 89 4 Comparative Example 7 0.13 98 >10 Comparative Example 8 0.41 70 2.5 Comparative Example 9 0.15 97 >10 Comparative Example 10 0.04 86 4 Comparative Example 11 0.18 94 >10

[0256] According to Table 1 above, Examples 1 and 2 showed low adhesion to aluminum, had appropriate hardness, and had an appropriate elasticity and tensile strength with a radius of curvature of 10 mm or less.

[0257] On the other hand, Comparative Examples 2 to 9 and Comparative Example 11 are 0.1 N / mm for aluminum 2 Since it has higher adhesive strength, it can be seen that it is difficult to ensure reworkability.

[0258] In addition, Comparative Examples 1, 4, 6 and 9 to 11 have a Shore 00 hardness greater than 85, so it can be seen that they are brittle and have low flexibility.

[0259] In addition, it can be seen that Comparative Examples 4, 7, 9, and 11 have a radius of curvature higher than 10 mm and do not have adequate elasticity and tensile strength.

[0261] Although the structure and features of the present application have been described above based on embodiments according to the present application, the present application is not limited thereto. It is obvious to those skilled in the art that various changes or modifications can be made within the spirit and scope of the present application, and therefore, it is noted that such changes or modifications fall within the scope of the appended claims.

Claims

Claim 1 A main part having a polyol component; and a curing agent part having an isocyanate component, wherein the main part comprises an alcohol compound or a thiol compound, the polyol component comprises a polymeric diol compound and a polymeric multiol compound, the polymeric diol compound is a polyether polyol, the polymeric multiol compound is a polyester polyol, and 0.1 N / mm with respect to aluminum 2 A curable composition that exhibits less than 85 adhesive strength and forms a cured product with a Shore 00 hardness of less than 85. Claim 2 In claim 1, the cured product is a curable composition having a thermal conductivity of 1.2 W / mK or higher. Claim 3 In claim 1, the cured product is a curable composition capable of forming a curved surface with a radius of curvature of less than 10 mm. Claim 4 delete Claim 5 In claim 1, the polyester polyol is a curable composition having a number average molecular weight in the range of 300 to 6,000 g / mol. Claim 6 delete Claim 7 In claim 1, the polyester polyol has a number average molecular weight in the range of 300 to 6,000 g / mol, and the number average molecular weight (M) of the polyester polyol n1 ) and the number average molecular weight (M) of the polyether polyol n2 The ratio of ) (M n1 / M n2 A curable composition in which ) is within the range of 0.5 to 2. Claim 8 In claim 1, the polyester polyol is a curable composition represented by the following chemical formula 1: [Chemical Formula 1] In the above Chemical Formula 1, R1 is an alkyl group, alkenyl group, or alkynyl group substituted or unsubstituted with a hydroxyl group; L1 and L2 are each independently a single bond, an alkylene group, an alkenylene group, or an alkynylene group; l and m may each be independently integers within the range of 0 to 10, and l+m is 1 or more; X1 and X2 are each independently an alkylene group, an alkenylene group, or an alkynylene group; Y1 and Y2 are each independently an alkylene group, an alkenylene group, or an alkynylene group; and R2 is a functional group represented by the following Chemical Formula 2, [Chemical Formula 2] In the above chemical formula 2, L3 is a single bond, an alkylene group, an alkenylene group, or an alkynylene group, X3 and Y3 are each independently an alkylene group, an alkenylene group, or an alkynylene group, and n is an integer in the range of 0 to 10. Claim 9 A curable composition according to claim 1, wherein the polyether polyol is a polyalkylene glycol. Claim 10 In claim 1, the polyol component is a curable composition comprising a polyester polyol in a ratio within the range of 30 to 70 weight%. Claim 11 A curable composition according to claim 1, wherein the polyol component comprises 50 to 120 parts by weight of polyether polyol per 100 parts by weight of polyester polyol. Claim 12 delete Claim 13 A curable composition according to claim 1, wherein the alcohol compound is a compound of the following chemical formula 3 and the thiol compound is a compound of the following chemical formula 4: [Chemical Formula 3] In Chemical Formula 3, R1 is a single bond, an alkylene group, an alkenylene group, or an alkynylene group, and R2, R3, and R4 are each independently hydrogen, an alkyl group, an alkenyl group, or an alkynylene group, [Chemical Formula 4] In Chemical Formula 4, R5 is a single bond, an alkylene group, an alkenylene group, or an alkynylene group, and R6, R7, and R8 are each independently hydrogen, an alkyl group, an alkenyl group, or an alkynylene group. Claim 14 A curable composition according to claim 1, comprising 5 to 60 parts by weight of an alcohol or thiol compound per 100 parts by weight of a polyester polyol. Claim 15 In claim 1, the subject part is a curable composition further comprising 300 to 2,000 parts by weight of a filler per 100 parts by weight of a polyol component. Claim 16 In claim 1, the curing agent part is a curable composition comprising a difunctional isocyanate compound and a polyfunctional isocyanate compound with three or more functions. Claim 17 In claim 16, the difunctional isocyanate compound is a curable composition in which the difunctional isocyanate compound is an aliphatic or alicyclic difunctional isocyanate compound. Claim 18 In claim 16, the polyfunctional isocyanate compound is a curable composition in which one or more are selected from a polymer of isocyanate compounds and a biuret compound of isocyanate compounds. Claim 19 In claim 16, the isocyanate component is a curable composition comprising 20 to 95 parts by weight of a difunctional isocyanate compound per 100 parts by weight of a polyfunctional isocyanate compound. Claim 20 A curable composition according to claim 1, wherein the curing agent part further comprises 500 to 3,000 parts by weight of a filler per 100 parts by weight of an isocyanate component. Claim 21 A curable composition according to claim 1, wherein the ratio (V1 / V2) of the volume of the main part (V1) and the volume of the curing agent part (V2) is within the range of 0.5 to 1.

5. Claim 22 A curable composition according to claim 1, wherein the main component part and the curing agent part are physically separated. Claim 23 A curable composition that is room temperature curable in claim 1. Claim 24 An apparatus comprising a heat-generating element; and a cooling portion, wherein the two are in thermal contact between the heat-generating element and the cooling portion, and the cured product of the curable composition of claim 1.

Citation Information

Patent Citations

  • Adhesive and Adhesive Tape

    KR101730462B1

  • Resin composition and battery module comprising the same

    KR1020190122450A

  • Resin Composition

    KR1020200055696A